PENERAPAN METODE PAIR CHECKS DENGAN MEDIA AUDIO YOUTUBE UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK (FAHMUL MASMU’) PELAJARAN BAHASA ARAB DI KELAS XI MA SITI MARIAM - Nur Izzah Alma’rifah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Listening skill is one of the most essential language skills as it serves as the foundation for language acquisition. Listening is not merely an activity of hearing sounds, but an active mental process that involves focusing attention, understanding, and capturing messages or ideas conveyed through spoken discourse. However, in learning fahmul masmu’ in Arabic language instruction, students’ listening skills are often found to be low due to the lack of varied teaching methods. This study aims to improve the learning process and outcomes of fahmul masmu’ among eleventh-grade students of MA Siti Mariam through the implementation of the pair checks method assisted by YouTube audio media. This research employed Classroom Action Research (CAR), conducted through the stages of planning, implementation, observation, and reflection. The pair checks method was applied by engaging students in pairs to listen to audio texts, discuss the content, and check each other’s understanding collaboratively. The results of the study indicate that the application of the pair checks method supported by YouTube audio media significantly improved students’ listening skills. This improvement is evidenced by an increase in the average listening test score from 70 in the initial condition to 84 after the implementation of the action. Therefore, the pair checks method is effective in enhancing fahmul masmu’ skills in Arabic language learning.